Zmiany na rynku róż ciętych w Unii Europejskiej - Jabłońska, Lilianna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The changes in the size and geographical structure of cut roses production in the world as well as in EU foreign trade have been studied. The direction and dynamics of cut roses imports and exports and trade balance have been analyzed. The main focus was to determine the geographic structure of EU trade, identifying the largest EU exporters and importers, export destinations and countries of import origin. The prices of imported cut roses according to origin have been analyzed as well. The study shows that the roses production in EU, also in Poland, is not competitive comparing to cheaper flowers from Africa. Growing demand will be satisfied by growing imports.